Parallel Problem Solving From Nature, PPSN XI 2010
DOI: 10.1007/978-3-642-15844-5_19
|View full text |Cite
|
Sign up to set email alerts
|

More Effective Crossover Operators for the All-Pairs Shortest Path Problem

Abstract: The all-pairs shortest path problem is the first non-artificial problem for which it was shown that adding crossover can significantly speed up a mutation-only evolutionary algorithm. Recently, the analysis of this algorithm was refined and it was shown to have an expected optimization time (w. r. t. the number of fitness evaluations) of Θ(n 3.25 (log n) 0.25 ).In contrast to this simple algorithm, evolutionary algorithms used in practice usually employ refined recombination strategies in order to avoid the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…This paper is an extension of the conference publication [10]. Here, we present full proofs and additionally discuss our structural insights in the new discussion section (Section 6).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This paper is an extension of the conference publication [10]. Here, we present full proofs and additionally discuss our structural insights in the new discussion section (Section 6).…”
Section: Introductionmentioning
confidence: 94%
“…To derive the two inequalities (10) and (12) in Proposition 13, we apply a result from [9], which we do not prove here but simply state as Lemma 14. We adapt the notation to our needs, a closer look into the proofs in [9] shows that this is easily possible.…”
Section: It Is Clear By Definition 10 and Definition 12 Thatmentioning
confidence: 99%
“…Speedups by crossover could be shown for coloring problems inspired by the Ising model [8,21] and for the all-pairs shortest path problem [3,5,4,16,11]. In terms of pseudo-Boolean optimization, most results were actually limited to artificial functions [13,22,19,20] constructed such that a theoretical analysis was possible.…”
Section: Introductionmentioning
confidence: 98%
“…There are several studies have contributed to this issue. For single optimization problems, these researches (Jansen and Wegener 2002;Kötzing, Sudholt, and Theile 2011;Lehre and Yao 2011;Doerr et al 2013;Doerr, Doerr, and Ebel 2015;Sudholt 2017;Doerr and Doerr 2018;Dang et al 2018) have shown that crossover operator can speed up the search. Specifically, they proved that EAs enabled crossover outperform the disabled ones on some benchmark discrete optimization problems in term of the expected running time.…”
Section: Introductionmentioning
confidence: 99%